2013
DOI: 10.1002/jcp.24252
|View full text |Cite
|
Sign up to set email alerts
|

Activation of nuclear estrogen receptors induced by low‐power laser irradiation via PI3‐K/Akt signaling cascade

Abstract: Low-power laser irradiation (LPLI) has been shown to exert promotive effects on cell survival and proliferation through activation of various signaling pathways. Estrogen receptors (ERs, ERα, and ERβ) are ligand-activated transcription factors, which regulate target gene expression, promote cell proliferation, and resist apoptosis. However, it is unclear whether LPLI could induce ligand-independent activation of ERs. In the present study, we investigated the subcellular pools, nuclear redistribution, and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 81 publications
1
10
0
1
Order By: Relevance
“…Proteins were extracted from cells using lysis buffer (20 mmol/L Tris, PH 7.4, 150 mmol/L NaCl, 2 mmol/L EDTA, 2 mmol/L ethyleneglycoltetraacetic acid(EGTA), 1 mmol/L sodium orthovanadate, 50 mmol/L sodium fluoride, 1% TritonX‐100, 0.1% SDS and 100 mmol/L phenylmethylsulfonyl fluoride). Western blot analysis was performed as previously described . Briefly, the extracts were mixed with Laemmli sample buffer (2% SDS) and placed in boiling water for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were extracted from cells using lysis buffer (20 mmol/L Tris, PH 7.4, 150 mmol/L NaCl, 2 mmol/L EDTA, 2 mmol/L ethyleneglycoltetraacetic acid(EGTA), 1 mmol/L sodium orthovanadate, 50 mmol/L sodium fluoride, 1% TritonX‐100, 0.1% SDS and 100 mmol/L phenylmethylsulfonyl fluoride). Western blot analysis was performed as previously described . Briefly, the extracts were mixed with Laemmli sample buffer (2% SDS) and placed in boiling water for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…In order to isolate cytosolic and nuclear extracts, RIN‐m cells, INS‐1 cells, and primary islets were washed twice with ice‐cold PBS and added with 250 µl of lysis buffer (10 mM Tris, pH 7.5, 10 mM NaCl, 3 mM MgCl 2 , 0.05% Nonidet P‐40, 1 mM EGTA, 1 mM sodium orthovanadate, 50 mM sodium fluoride, 100 µM phenylmethylsulfonyl fluoride, 10 µg/ml leupeptin, 10 µg/ml aprotinin, 5 µg/ml pepstatin A, and 1 nM okadaic acid). Cytosolic and nuclear extracts were obtained as described previously [Huang et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Light energy is absorbed by intracellular chromophores, which accelerate electron transfer reactions, leading to increase the intracellular levels of Ca 2+ and reactive oxygen species as versatile second messengers [Lan et al, ]. The current studies have shown that LPLI is involved in multiple cellular physiological functions, including gene transcription and protein expression [Huang et al, ], cytoskeleton reorganization [Ricci et al, ], and cell migration [Karunarathne et al, ]. In addition, it has been widely employed in neck pain care [Chow et al, ], skin anti‐aging [Ling et al, ], and wound healing [Ozcelik et al, ].…”
mentioning
confidence: 99%
“…A growing body of experimental and clinical studies has demonstrated that LPLI may regulate cell survival, proliferation, and differentiation by triggering a series of complex intracellular signaling events (Feng et al , 2012, Huang et al , 2013, Liang et al , 2012, Ling et al , 2014, Meng et al , 2013. This has attracted the interest of researchers to study the effect and molecular mechanism of LPLI on the broad spectrum of cellular processes.…”
Section: Introductionmentioning
confidence: 97%